Proximal opening wedge metatarsal osteotomy for correction of moderate to severe hallux valgus deformity using a locking plate - Badekas, Athanasios (Springer Berlin Heidelberg, 2013)
PURPOSE: Hallux valgus is a complex deformity of the first metatarsophalangeal joint, with varus angulation of the first metatarsal, valgus deviation of the great toe and lateral displacement of the sesamoids and the extensor tendons. The aim of the surgery is to achieve correction of the varus deviation of the 1st metatarsal which is considered by some as the primary intrinsic predisposing factor to hallux valgus deformity. METHODS: We retrospectively reviewed 85 patients (107 feet) who underwent an opening wedge osteotomy of the 1st metatarsal for correction of moderate to severe hallux valgus and metatarsus primus varus. A medially applied anatomic pre-contoured locking plate was used for fixation of the osteotomy. RESULTS: The mean IMA was decreased from 15.8 (range 12–22) degrees to 7.8 (range 0–12) degrees. The mean pre-operative HVA was 39 (range 21–52) degrees and the mean postoperative HVA was 11.8 (6–19) degrees. The pre-operative AOFAS score was 52 (SD 3.1) and the postoperative score was 85 (SD 5.2). CONCLUSION: The proximal opening wedge metatarsal osteotomy is a safe, effective and reproducible technique for correction of moderate to severe hallux valgus deformity. The use of a locking plate provides enough control at the fragments, enhancing healing of osteotomy and maintenance of the correction even with a violated proximal lateral cortex.